Sinestesia dalam Novel "Tanjung Kemarau" Karya Royyan Julian - Milliana Milliana; Moh Badrih (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2022)
Synesthesia is change. the meaning of the word form due to the use of responses from the two senses. This research discusses; what are the types and meanings of synesthesia contained in the novel Tanjung Kemarau by Royyan Julian. The method used in this research is descriptive qualitative with semantic studies. Data was collected by reading and note-taking techniques. Meanwhile, the data analysis used in the study, namely; transcribing, identifying, copying, analyzing, rechecking, and concluding. The novel found five types of synesthesia, namely; changes in the response of the sense of taste to the sense of sight, changes in the response of the sense of touch to the sense of hearing, changes in the response of the sense of touch to the sense of sight, changes in the response of the sense of sight to the sense of hearing, and changes in the response of the sense of hearing to the sense of sight. In addition, there are five meanings of synesthesia in it, namely the meaning based on the context of feeling (feeling), the setting context, the context of the goal, the context of tone, and the meaning of synesthesia based on the context of the relationship.Keyword: language;  novel; synesthesia; semantics Abstrak:Sinestesia  adalah  perubahan. makna bentuk kata akibat penggunaan tanggapan dari kedua indra. Penelitian ini membahas; apa saja jeniss dan makna sinestesia yang terdapat dalam novel Tanjung Kemarau  karya Royyan Julian, Metode yang digunakan dalam penelitian ini adalah kualitatif deskriptif dengan kajian semantik. Pengumpulan data dilakukan dengan teknik baca dan catat Sedangkan  analisis data yang digunakan dalam penelitian, yaitu; mentranskrip, mengidentifikasi, menyalin, menganalisis, pengecekan ulang, dan menyimpulkan. Dalam novel ditemukan lima  jenis-jenis sinestesia yakni; perubahan tanggapan indra perasa ke indra penglihatan, perubahan tanggapan indra peraba ke indra pendengaran, perubahan tanggapan indra peraba ke indra penglihatan, perubahan tanggapan indra penglihatan ke indra pendengaran, dan perubahan tanggapan indra pendengaran ke indra penglihatan. Selain itu, ada lima makna sinestesia di dalamnya yakni makna berlandaskan konteks perasaan (felling), konteks setting, konteks tujuan, konteks nada, dan makna sinestesia berlandaskan konteks relasiKata kunci: bahasa; novel; sineastesia; semantik